Penanganan Terorisme: Perspektif Psikologi - Rena Latifa (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
This paper is a literature study on the roots of terrorism and alternative interventions that can be applied. The root of terrorism described in macro social standpoint, the system of government and politics, religion and ideology doctrination. Meanwhile, from the standpoint of the psychological explained about the special characters mediating the terrorist acts of aggressive behavior. The formation of social identity also participating whenever individual joined the terrorist organization. Intervention offered based on several literature findings. Jerrold (2005) focuses on preventing the entry of young people in a terrorist organization by the monitoring system of education, especially religious education. Rivera & Hancock (2003) mentions several psychological strategies in the fight against terrorism: the Anti-Terrorism, Counter-Terrorism, and Consequence Management. Woolf & Hulsizer (2005) offers a range of psychosocial model of primary prevention, secondary prevention and intervention.Keywords: terrorism, terrorist, intervention